2009
DOI: 10.1200/jco.2008.18.1545
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Concurrent Cisplatin-Radiotherapy With or Without Neoadjuvant Docetaxel and Cisplatin in Advanced Nasopharyngeal Carcinoma

Abstract: Neoadjuvant docetaxel-cisplatin followed by CRT was well tolerated with a manageable toxicity profile that allowed subsequent delivery of full-dose CRT. Preliminary results suggested a positive impact on survival. A phase III study to definitively test this neoadjuvant-concurrent strategy is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
433
8
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 489 publications
(460 citation statements)
references
References 40 publications
16
433
8
3
Order By: Relevance
“…Of the last 14 articles, two trials were almost the same in design and data with different authors (Sun et al, 2009;Zhong et al, 2011), and then zhong et al's trial (Zhong et al, 2011) was discarded. Another two trials (Chan et al, 2005;Hui et al, 2009) were the same in design and data with almost the same authors but different numbers of patients, and in order to avoid data reduplication, then Chan et al's trial (Chan et al, 2005) was discarded. Two trials (Fountzilas et al, 2009;Fountzilas et al, 2012) were from the same study but were reported in different follow-ups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the last 14 articles, two trials were almost the same in design and data with different authors (Sun et al, 2009;Zhong et al, 2011), and then zhong et al's trial (Zhong et al, 2011) was discarded. Another two trials (Chan et al, 2005;Hui et al, 2009) were the same in design and data with almost the same authors but different numbers of patients, and in order to avoid data reduplication, then Chan et al's trial (Chan et al, 2005) was discarded. Two trials (Fountzilas et al, 2009;Fountzilas et al, 2012) were from the same study but were reported in different follow-ups.…”
Section: Resultsmentioning
confidence: 99%
“…All satisfied the criteria of complete outcome data (He et al, 2009;Hui et al, 2009;Ma et al, 2009;Sun et al, 2009;He et al, 2011;Ruste et al, 2011;Xu et al, 2011;Chen et al, 2012;Cui et al, 2012;Fountzilas et al, 2012;Huang et al, 2012), two studies didn't satisfied the item of selective reports He et al, 2011). There were no studies reporting allocation concealment, binding of participants and personnel, and binding of outcome assessment.…”
Section: Risk Of Bias Of Eligible Studies (Figure 2)mentioning
confidence: 99%
See 3 more Smart Citations